Efektivitas Pengawasan Majelis Pengawas Daerah Terhadap Notaris yang Meninggalkan Wilayah Jabatan - Aini, Nurina; Ilmar, Aminuddin; Arisaputra, Muhammad Ilham (Universitas Widya Gama Malang, 2023)
This study aims to analyze and explain the form of responsibility of the supervisors of the Regional Supervisory Board (MPD) towards notaries who leave their territory of office without valid reasons and formulate and identify the effectiveness of the supervisory function of the Regional Supervisory Council (MPD) against notaries who leave their territory of office without valid reasons. This research is an empirical legal research. The research was conducted in Makassar City, South Sulawesi. The results of the study show that the supervision carried out on a Notary is intended so that the Notary in carrying out his duties is based on the rules according to the provisions of the laws and regulations governing the position of a Notary. The laws and regulations governing office do not only require laws or laws, but also based on the trust given by the parties to the notary. Notaries must act professionally in carrying out their duties, because the position of Notary is a position of trust that must be aligned with those who carry out the duties of a Notary's position as a person who can be trusted. Notary as a position of trust does not mean anything if it turns out that those who carry out their duties as a Notary are people who cannot be trusted, including leaving their area of office without a valid reason.